Pemisahan Psikologis dan Penyesuaian Diri di Kehidupan Kampus pada Mahasiswa Baru yang Merantau - Ulifa (Ilmu Psikologi Universitas Yudharta Pasuruan, 2023)
The purpose of this study was to determine the relationship of psychological separation and college adjustment in migrated new college students. The method used in this research is quantitative correlational. There are three sample criteria used: new students active in tertiary institutions, migrated students and single. The sampling technique used was accidental sampling with a total of 769 respondents. This study uses two scales that have been through the stages of adaptation, namely Psychological Separation Inventory (PSI) and Inventory of New College Student Adjustment (INCA). The hypothesis testing technique used is the Pearson product moment correlation with a result of pearson correlation 0.322 and p-value 0,000 (p <0.05). The results showed there is a positive relationship between psychological separation and college adjustment in migrated new college students